High availability and disaster recovery options for DB2 on Linux, UNIX, and Windows - Bartkowski, Stanislaw (IBM redbooks., 2012)
As organizations strive to do more with less, IBM® DB2® for Linux, UNIX, and Windows provides various built-in high availability features. DB2 further provides high availability solutions by using enterprise system resources with broad support for clustering software, such as IBM PowerHA® SystemMirror®, IBM Tivoli® System Automation for Multiplatforms (Tivoli SA MP), and Microsoft Windows Cluster Server. This IBM Redbooks® publication describes the DB2 high availability functions and features, focusing on High Availability Disaster Recovery (HADR) in the OLTP environment. The book provides a detailed description of HADR, including setup, configuration, administration, monitoring, and preferred practices. This book explains how to configure Cluster software PowerHA, Tivoli SA MP, and MSCS with DB2 and show how to use these products to automate HADR takeover. DB2 also provides unprecedented enterprise-class disaster recovery capability. This book covers single system view backup, backup and restore with snapshot backup, and the db2recovery command, in detail. This book is intended for database administrators and information management professionals who want to design, implement, and support a highly available DB2 system.